Indeks Pelayanan Publik: Konsep, Dasar Hukum, dan Implementasi dalam Pengukuran Kinerja Layanan - Mozin, Sri Yulianty; Siti Fatimah; Fadila Al-Hamid (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This article discusses the concept, legal basis, and implementation of the Public Service Index (PSI) in measuring public service performance in Indonesia. PSI is a measurement tool used to assess the quality of public services provided by government agencies to the public. This study employs a qualitative approach with literature review and document analysis methods. The findings indicate that PSI plays a crucial role in enhancing accountability and transparency in public service delivery. However, the implementation of PSI still faces various challenges, such as limited human resources and inadequate infrastructure. Therefore, collaborative efforts between the government, society, and the private sector are necessary to improve the effectiveness of PSI in measuring public service performance.